Publisher Correction: Melting conditions in the modern Tibetan crust since the Miocene - Jinyu Chen; Fabrice Gaillard; Arnaud Villaros; Xiaosong Yang; Mickael Laumonier; Laurent Jolivet; Martyn Unsworth; Leїla Hashim; Bruno Scaillet; Guillaume Richard (Nature Communications, 2018)
The original PDF version of this Article contained an error in which Fig. 3 and its legend were omitted and Equations 5 and 6 contained errors.This has been corrected in the PDF version of the Article. The HTML version was correct from the time of publication.